Genetic Diversity Analysis in 27 Tomato Accessions Using Morphological and Molecular Markers - Catur Herison; Surjono H. Sutjahjo; Ineu Sulastrini; Rustikawati Rustikawati; Siti Marwiyah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Genetic diversity is the most important aspect in tomato breeding activities. Better assessment on the diversity of the collected accessions will come up with better result of the cultivar development. This study aimed at analyzing the genetic diversity of 27 tomato accessions by morphological and molecular markers. Twenty seven accessions collected from various regions of Indonesia were planted in the field and evaluated for their morphological traits, and RAPD analyzed for their molecular markers. The UPGMA clustering analyzes, elaborating the combination of morphological and molecular data, indicated that the tomato accessions could be grouped into 5 major groups with 70 % genetic similarity levels. Current study indicated that although many accessions came from different locations, they congregated into the same group. Cherry, Kudamati 1 and Lombok 3 were the farthest genetic distant accessions to the others. Those three genotypes will be the most valuable accessions, when they were crossed with other accessions, for designing a prospective breeding program in the future.